How much vocabulary is needed to use English? Replication of van Zeeland & Schmitt (2012), Nation (2006) and Cobb (2007). (2nd March 2015) - Schmitt, Norbert; Cobb, Tom; Horst, Marlise; Schmitt, Diane
Abstract : There is current research consensus that second language (L2) learners are able to adequately comprehend general English written texts if they know 98% of the words that occur in the materials. This important finding prompts an important question: How much English vocabulary do English as a second language (ESL) learners need to know to achieve this crucial level of known-word coverage? A landmark paper by Nation (2006 ) provides a rather daunting answer. His exploration of the 98% figure through a variety of spoken and written corpora showed that knowledge of around 8, 000–9, 000 word families is needed for reading and 6, 000–7, 000 for listening. But is this the definitive picture? A recent study by van Zeeland & Schmitt (2012 ) suggests that 95% coverage may be sufficient for listening comprehension, and that this can be reached with 2, 000–3, 000 word families, which is much more manageable. Getting these figures right for a variety of text modalities, genres and conditions of reading and listening is essential. Teachers and learners need to be able to set goals, and as Cobb's study of learning opportunities (2007 ) has shown, coverage percentages and their associated vocabulary knowledge requirements have important implications for the acquisition of new word knowledge through exposure to comprehensible L2 input. This article proposes approximate replications of Nation (2006 ), van Zeeland & Schmitt (2012 ), and Cobb (2007 ), in order to clarify these key coverage and size figures.